Barriers to Independent Non-Executive Directors’ Effectiveness in Performing Their Roles - Annuar, Hairul Azlan (2010)
Purpose – The overall purpose of the research presented is to ascertain whether independent non-executive directors (INEDs) in Malaysian public listed companies (PLCs) may be facing certain barriers in the performance of their roles. The findings may provide helpful insights to Arab businessmen who wish to do business in Malaysia, notably with PLCs, as they may depend upon local INEDs to protect their investments and to act on their behalf. The absence of barriers to the performance of INEDs’ role may provide these businessmen with the confidence and added assurance to invest safely and profitably in Malaysia. Design/methodology/approach – A qualitative approach, consisting of a series of interviews with board members, was chosen. The sampling frame was made as large as possible and for the purpose of this study, consisted of board members who sit on publicly listed companies (PLCs) of the main board and Malaysian-owned.